Light‐emitting diode phototherapy for neonatal hyperbilirubinemia: A literature review - Widhiastuti, Erma (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Neonatal hyperbilirubinemia is a problem that often occurs in newborns who must be separated between mother and baby due to phototherapy. Clinically, jaundice or symptoms of changes in the sclera, mucous membranes and skin becoming yellow can be seen if there is an increase in the bilirubin concentration of more than 5 mg/dl. In most infants, the development of unconjugated hyperbilirubinemia is a normal transition. However, in some babies plasma levels can increase excessively, this can be a concern because bilirubin is not conjugated so it is neurotoxic and can cross the blood brain barrier, causing brain damage.Purpose: To provide an overview of the results of a literature review regarding the effectiveness of light emitting diode (LED) phototherapy in reducing total serum bilirubin (TSB) levels.Method: The literature review study used the preferred reporting items for systematic reviews and meta-analyses (PRISMA) to conduct systematic observations, a prospective comparative study, a randomized controlled trial, a retrospective chart review, and two prospective studies. Based on article searches, 1.270 articles were successfully extracted, resulting in 12 full text articles that were relevant to the topic of discussion.Results: Various research results show that LED lights have better effectiveness in reducing TSB levels. All phototherapy methods are effective in reducing TB within safe limits. Mounting evidence suggests that dual LED phototherapy is effective for the management of hyperbilirubinemia in neonates.Conclusion: Phototherapy using LED lights in the form of bags or blankets is more effective in reducing bilirubin levels more quickly compared to compact fluorescent lights or conventional phototherapy. Keywords: Hyperbilirubin; Newborn; Phototherapy Light Emitting Diodes. Pendahuluan: Hiperbilirubinemia neonatal merupakan masalah yang sering terjadi pada bayi yang baru lahir, yang terpaksa memisahkan ibu dan bayi karena dilakukan fototerapi. Secara klinis, ikterik atau suatu gejala perubahan sklera, membran mukosa, dan kulit menjadi kuning dapat dilihat ketika terjadi kenaikan konsentrasi bilirubin lebih dari 5 mg/dl. Pada sebagian besar bayi, kejadian hiperbilirubinemia tidak terkonjugasi merupakan transisi normal. Namun, pada beberapa bayi kadar plasma mungkin meningkat berlebihan, hal ini dapat menjadi perhatian karena bilirubin tidak terkonjugasi sehingga bersifat neurotoksik dan dapat melewati sawar darah ke otak yang menyebabkan kerusakan otak.Tujuan: Untuk memberikan gambaran dari hasil review literatur tentang efektifitas fototerapi light emitting diode (LED) dalam mengurangi kadar total serum bilirubin (TSB).Metode: Penelitian literature review menggunakan preferred reporting items for systematic reviews and meta-analysis (PRISMA) untuk melakukan tinjauan sistematis, prospective comparative study, randomized controlled trial, retrospective chart review, dan two prospective study. Berdasarkan pencarian artikel didapatkan sebanyak 1.270 artikel yang diekstraksi hingga mendapatkan 12 artikel full text yang relevan dengan topik pembahasan.Hasil: Berbagai hasil penelitian menunjukkan sinar LED memiliki efektivitas lebih baik untuk menurunkan kadar TSB. Semua metode fototerapi efektif menurunkan TSB dalam batas aman. Banyak bukti menunjukkan bahwa fototerapi LED ganda adalah efektif untuk penatalaksanaan hyperbilirubinemia pada neonates.Simpulan: Fototerapi yang menggunakan sinar LED dan berbentuk kantong atau selimut lebih efektif lebih cepat dalam menurunkan kadar bilirubin dibandingkan dengan fototerapi compact fluorescent light atau konvensional. Kata Kunci : Bayi Baru Lahir; Fototerapi Light Emitting Diode; Hiperbilirubin.